Implementation of Application and Product System (SAP) in Metal Coating Process Manufacturing Company - Widya, Adi Rusdi; Supriyanti, Supriyanti (Journal of INISTA, 2023)
In the development of the Industrial Revolution 4.0 era, the use of an Enterprise Resource Planning System is a long-term investment for a company to improve efficiency, performance, and decision-making tools for the company. In general, it uses a centralized database for various business processes to reduce manual labor and simplify existing business workflows. ERP systems usually contain Dashboards where users can view real-time data collected from across the business to measure productivity and profitability. This means that any data or information received will be updated immediately as soon as the user inputs the data into the time system even though the data has been closed, the company can know and control the condition of the company every day and can control a production process so that decision making can be done quickly, carefully, and precisely because it is based on valid internal data and is always up to date. there is still a difference in data between the transaction process, The purpose of the research is to process information in real-time and accurately, The research stage begins with a literature study, hardware prototypes, and making programs, The results of the research are an increase in transaction accuracy of 43% after SAP implementation is optimally implemented.